Respuesta :

Simplifying 25 + -4x = 15 + -3x + 10
Reorder the terms: 25 + -4x = 15 + 10 + -3x
Combine like terms: 15 + 10 = 25 25 + -4x = 25 + -3x
Add '-25' to each side of the equation. 25 + -25 + -4x = 25 + -25 + -3x
Combine like terms: 25 + -25 = 0 0 + -4x = 25 + -25 + -3x -4x = 25 + -25 + -3x Combine like terms: 25 + -25 = 0 -4x = 0 + -3x -4x = -3x Solving -4x = -3x
Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right.
Add '3x' to each side of the equation. -4x + 3x = -3x + 3x
Combine like terms: -4x + 3x = -1x -1x = -3x + 3x
Combine like terms: -3x + 3x = 0 -1x = 0
Divide each side by '-1'. x = 0
Simplifying x = 0